The Strategic Role of Human Resource in Enhancing Islamic Educational Quality: A Literature Review - Okta Iwan Setiawan; Iis Susanti; Chairun Nisa Male; Eti Hadiati; Junaida Junaida (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
Human Resource Management has become a strategic concern in educational institutions because educational quality is strongly influenced by the competence, motivation, performance, and professional sustainability of educators and education personnel. This study aims to critically examine the role and functions of Human Resource Management in enhancing educational quality through a systematic literature review. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines. Literature was collected from Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis Online, Emerald Insight, Google Scholar, Garuda, SINTA, and Crossref, focusing on peer-reviewed studies published between 2018 and 2025. From 436 initially identified records, 32 articles met the inclusion criteria and were analyzed through thematic synthesis. The findings identified five interconnected dimensions of Human Resource Management that consistently contribute to educational quality: strategic workforce planning and recruitment, professional development, performance management, leadership and motivation, and quality assurance. The analysis shows that effective recruitment ensures the availability of qualified educators, while continuous professional development enhances pedagogical and professional competencies. Furthermore, performance management systems strengthen accountability and productivity, whereas leadership and motivation increase organizational commitment, job satisfaction, and work engagement. Quality assurance practices were also found to support institutional effectiveness and continuous improvement. This study contributes to the literature by providing a comprehensive synthesis of recent evidence on how integrated Human Resource Management practices influence educational quality. The study concludes that Human Resource Management functions most effectively when implemented as a strategic system that aligns human resource development with institutional goals, thereby supporting sustainable educational improvement and organizational excellence. Keywords: Educational quality; Human Resource Management; Performance management; Professional development; Systematic literature review